Desenvolvimento de sistema polimérico mucoadesivo a base de quitosana e condroitina para veiculação de substâncias antiglaucomatosas. - Larissa Caldeira Navarro (2019)
The term glaucoma refers to a group of diseases characterized by retinal ganglion cells death and optic nerve degeneration. The treatment focuses on pharmacological treatment through the instillation of eye drops with several drawbacks, such as: discomfort and difficulty in instillation; forgetfulness of application; low bioavailability of the drug. These drawbacks lead to poor adherence to treatment and unnecessary systemic exposure leading to adverse side effects. An alternative to eye drops are sustained drug delivery systems, which ensure maintenance of a therapeutically effective concentration for an extended period. The aim of this work was to develop a polymer system for the delivery of antiglautomatous substances, guaranteeing an adequate therapeutic level, and eliminating the need for multiple dose pharmacotherapy, thus increasing adherence and treatment efficacy. Chitosan is a biodegradable, safe and bioactive natural polymer. Chondroitin is capable of forming polyelectrostatic complexes with amines (in this case, chitosan). The complex formed between these two polymers presents ideal characteristics to be used as ocular inserts, in a safe and effective way since both polymers are biodegradable and biocompatible. The inserts produced with these polymers were physicochemically characterized by infrared spectrometry, thermal analysis, hydration potential, surface pH, mucoadhesion capacity, release capacity of the active substances in vitro and in vivo. No significant interactions were observed in infrared spectra. This result was confirmed by the DSC thermograms. The hydration capacity was of 400% demonstrating mechanical resistance and swelling ability of the films. The active substances were released in the in vitro test in approximately 30 minutes and in the in vivo test the release of the active substance occurred for 3 consecutive weeks of treatment. After histological analysis of the optic nerve of the guinea pigs, it was possible to observe that there was no degradation (excavation) of the optic nerve. These results demonstrate that the inserts are layers of releasing the active substance in vivo and protecting the ganglion cells and may therefore be a viable alternative to conventional eye drops treatment.